Enhancing Pharmacovigilance in Pharmaceutical Companies: A Comparative Study of Electronic Reporting Before and After Implementation - Meknassi Salime, Ghita; Bhirich, Nihal; Asraoui, Abdelghani; Hassan El Karimi, Moulay El; Rahali, Younes; Sefiani, Houda (Current Drug Safety, 2025)
<span class=
Keywords: Adverse drug reaction reporting systems